2015
DOI: 10.1186/s12887-015-0528-z
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of suspected developmental delays in early infancy: results from a regional population-based longitudinal study

Abstract: BackgroundPrevalence estimates on suspected developmental delays (SDD) in young infants are scarce and a necessary first step for planning an early intervention. We investigated the prevalence of SDD at 4, 6 and 12 months, in addition to associations of SDD with gender, prematurity and maternal education.MethodsThis study is based on a Norwegian longitudinal sample of 1555 infants and their parents attending well-baby clinics for regular health check-ups. Moreover, parents completed the Norwegian translation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
71
3
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(86 citation statements)
references
References 48 publications
6
71
3
6
Order By: Relevance
“…Another study found reduced expression and activity of placental 11β-HSD2 (a placental enzyme that protects the fetus from harmful effects of stress) in male fetuses compared to their female counterparts [30, 32]. Finally, many epidemiological studies have shown that fetal morbidity/mortality, neurodevelopmental alterations, and pregnancy complications are more associated with male fetuses than females [10, 33]. The underlying mechanisms in these male-female fetal differences have not been elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Another study found reduced expression and activity of placental 11β-HSD2 (a placental enzyme that protects the fetus from harmful effects of stress) in male fetuses compared to their female counterparts [30, 32]. Finally, many epidemiological studies have shown that fetal morbidity/mortality, neurodevelopmental alterations, and pregnancy complications are more associated with male fetuses than females [10, 33]. The underlying mechanisms in these male-female fetal differences have not been elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Studies generally support the ability of the ASQ/ASQ:SE to effectively and feasibly detect children with suspected developmental–behavioural problems and to determine typical developmental pathways . However, no Scandinavian ASQ‐3 norming and/or validation studies, or ASQ:SE‐2 norming studies, were found in our literature search.…”
Section: Resultsmentioning
confidence: 84%
“…Results for Scandinavian children with concerning screens from the ASQ/ASQ:SE were quite inconsistent compared with US studies where, at a minimum, children were routinely referred to Individuals with Disabilities Education Act EI/ECSE programmes (which are available in every county of every state). These Scandinavian children often had no clearly described follow‐up plan, or they received further assessment (typically with a psychologist or medical subspecialist) based on individualized research protocols . The literature also collectively indicates different follow‐up procedures in different regional municipalities throughout Denmark, Norway, and Sweden .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations